A new damage evolution model to estimate the creep fracture behavior of brazed joint under multiaxial stress. (December 2018) - Luo, Yun; Jiang, Wenchun; Zhang, Yu-cai; Zhou, Fan; Tu, Shan-Tung
Highlights: A new model was proposed to reasonably predict creep life. The notch weakening effect was found in the brazed joint. The creep life increases with notch angle increases while it decreases with notch radius increases. The brazed joint under multiaxial stress was mainly fractured by intergranular brittle mode. Abstract: The brazed components operating at high temperature inevitably suffer from multiaxial creep under multiaxial stress. In this study, the creep strain, fracture and failure mechanisms of HastelloyC276-BNi2 brazed joint under multiaxial stress were studied by experiment and finite element modeling (FEM). A new damage evolution model was put forward to estimate the creep fracture behavior of brazed joint under multiaxial stress. And the influences of notch angle and radius were also discussed. The notch weakening effect was exhibited in the brazed joints. The creep life is not only dependent on the creep fracture strain but also on notch type. The proposed creep damage evolution model can reasonably reflect the relationship between creep fracture ductility and multiaxiality. The predicted creep life by proposed model agrees very well with the experimental results. Most importantly, the fracture mechanisms of brazed joint under multiaxial stress were revealed and the creep damage evolution was well interpreted by FEM. Graphical abstract: Image, graphical abstract